Plateau pikas lead to higher rhizome and root-derived bud densities and their contribution to total belowground bud density in alpine grasslands - Wang, Ni; Wang, Qian; Pang, Xiao Pan; Guo, Zheng Gang (Frontiers in Plant Science, 2025)
Plant belowground buds are important agents for examining the effects of small semi-fossorial herbivores on plant population regeneration in perennial grasslands. In this study, we used the plateau pika (Ochotona curzoniae) as a focally small semi-fossorial herbivore to investigate its effects on tiller, rhizome, and root-derived bud densities. The study was conducted in alpine grasslands from Gangcha County to Gonghe County in Qinghai Province, China. A paired experimental design was employed, with 20 plots established in areas with plateau pikas and 20 plots plateau pikas established in without plateau pikas. The results indicated that total belowground, rhizome, and root-derived bud densities were 49.31%, 84.68%, and 91.73% higher in the presence than in absence of plateau pikas, respectively. The contributions of rhizome and root-derived buds to total belowground buds were 8% and 3% higher in the presence than in the absence of plateau pikas, respectively, whereas the contribution of tiller buds to total belowground buds was 11% lower in the presence than in the absence of plateau pikas. Total belowground buds were positively correlated with soil moisture and negatively correlated with plant aboveground biomass in the absence of plateau pikas. In contrast, they were positively correlated with total soil phosphorus and rhizome biomass in the presence of plateau pikas. These results suggested that the phosphorus supplementation is an alternative way to improve plant population regeneration and facilitate alpine grassland sustainability when plateau pikas are present in alpine grasslands.